If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -10 = 12 + -1x Reorder the terms: -10 + x = 12 + -1x Solving -10 + x = 12 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -10 + x + x = 12 + -1x + x Combine like terms: x + x = 2x -10 + 2x = 12 + -1x + x Combine like terms: -1x + x = 0 -10 + 2x = 12 + 0 -10 + 2x = 12 Add '10' to each side of the equation. -10 + 10 + 2x = 12 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = 12 + 10 2x = 12 + 10 Combine like terms: 12 + 10 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 6ln(x)=-1 | | 8w*2=50 | | 6lnx=-1 | | 180-7x=29+16 | | x+6y-5x-11y+2x= | | 35x-7=35x-7 | | 5m^3+4mn+5m^2+4n= | | 3x^2y^2+2x^3y+9xy^2= | | x+6y-6x-13y+2x= | | 3/21+4/21 | | 1/9+1/3+1/6 | | 4/8+1/8 | | 62.10=(20+.5x)+.15(20+.5x) | | 5/8-2/5 | | (10x)(5x)= | | T(30)=3.8(30)-2.5 | | 3xyz+2zxy-7zyx+2xy= | | -5a^2b^3-(-3)a^2b^2= | | x^4+4x^3+8x^2+8x-3=0 | | 4/20+12/20 | | -5a^2b^3-(-3a^2b^2)= | | 5r+15=6r-10 | | 2xy-3xyz= | | -6y+13=-18y-23 | | y+10=-(x-15) | | 5u+2v-2(4u-5v)= | | .75(.25x+8)-(25x+2)=0.375(4-x)-.25x | | X/19=5/95 | | -6y-12=-18y-23 | | 6x-12=x-22 | | y-2=3(x+1) | | 15/45=x/12 |